Synthesis of unsymmetrically tetrasubstituted pyrroles and studies of AIEE in pyrrolo[1, 2-a]pyrimidine derivatives. Issue 19 (25th April 2022) - Li, Taian; Chiou, Mong-Feng; Li, Yajun; Ye, Changqing; Su, Min; Xue, Mengyu; Yuan, Xiaobin; Wang, Chuanchuan; Wan, Wen-Ming; Li, Daliang; Bao, Hongli
Abstract : A novel method for the challenging synthesis of unsymmetrically tetrasubstituted NH-pyrroles from chalcone derivatives is reported. The pyrrolo[1, 2- a ]pyrimidine derivatives that were synthesized from NH-pyrroles exhibit AIE and AIEE property. Abstract : Pyrroles are among the most important heterocycles in pharmaceuticals and agrochemicals. Construction of pyrrole scaffolds with different substituents and a free NH group, however, is challenging. Herein, a metal-free method for the synthesis of unsymmetrically tetrasubstituted NH-pyrroles using a consecutive chemoselective double cyanation is reported. The desired pyrroles were obtained with yields up to 99% and good functional group tolerance. Mechanistic studies identified a reaction mechanism that features a subtle sequence of first cyano-addition and migration, followed by cyano-addition and aromatization to afford the pyrrole skeleton. Pyrrolo[1, 2- a ]pyrimidines are synthesized as the synthetic applications of NH-pyrroles, and these pyrrolo[1, 2- a ]pyrimidines exhibit unpredicted time-dependent aggregation-induced emission enhancement (AIEE) properties.